Increasing the competency of prospective coffee entrepreneurs through experiential training in coffee tourism village: Case study of young entrepreneurs in Indonesia - Christian Wiradendi Wolor; Datu Razali Datu Eranza; Mahmoud Ali Rababah; Wong Chee Hoo; Ahmad Nurkhin; Yumiad Fernando Richard; Abdullah Rahman (International information and engineering technology association, 2024)
The growth of the coffee business has not been accompanied by an increase in entrepreneurship, one of the causes being a lack of competence which can hinder the development of new businesses. This research aims to understand and explore how entrepreneurs improve skills in the coffee business through experience-based training conducted at Malabar Mountain Coffee. This study provides academic and practical contributions to creating skilled entrepreneurs towards the Indonesian government's target of 1 million new young entrepreneurs. This refers to the Indonesian government's target to develop the economy and encourage the development of the business world in Indonesia. This research uses a qualitative methodology, specifically using a case study approach. Data was collected using observation and semi-structured interviews. Direct observations and interviews were carried out by established standards to answer research questions. Then the data is analysed, and an explanation of the findings obtained from this investigation is given. The research results found that all participants improved their skills through the experiential training they received. This has a very positive impact on increasing participants' competence in the form of skills in choosing the coffee they will sell later and also serving good coffee drinks to consumers.